Politeness Strategies On Apologizing Expression Of “The Princess Diaries” - Gulo, Lestari; Afriana, Afriana (LPPM Universitas Putera Batam, 2024)
This study aims to examine the politeness methods used by the characters in their apology expressions. The study was designed as a descriptive and qualitative research. The data were examined using descriptive techniques, applying various politeness methods suggested by Brown and Levinson (1987) to identify different types of politeness tactics. The Princess Diaries, an American romantic-comedy movie released in 2001, provided the statistical data. Using Brown and Levinson's Politeness Strategies (1987), the analysis findings show that 10 utterances can be categorized as expressions of regret. According to Brown and Levinson's politeness theory, negative politeness is used to show respect so as not to offend the interlocutor, while positive politeness occurs among a group of friends and family members who have a close relationship with the interlocutor. Therefore, it can be said that all the characters in the movie who use positive politeness to show regret are female, and positive politeness is the politeness technique they use most often.